The Influence of the Project Citizen Model on Elementary School Students' Critical Thinking Skills - Irwan Kurniawan; Shely Cathrin (Journal of Educational Sciences, 2026)
This study aims to analyze the influence of the Project Citizen model on the critical thinking skills of elementary school students. The main problem in learning Civic Education in elementary schools is the low critical thinking skills of students due to the dominance of conventional approaches that focus on one-way learning. This study uses a quantitative approach with a quasi-experimental design, involving two groups: an experimental class that applies the Project Citizen model and a control class that uses conventional learning. The research instrument is a test. The results of the analysis show that the average pre-test score of 50.48 increased to 74.04 in the post-test after the implementation of Project Citizen. The independent t-test showed a significance value of 0.019 <0.05, which means there is a significant influence between the implementation of the Project Citizen model on improving students' critical thinking skills. In addition, the implementation of this model also increases participation and effective communication between students. Thus, Project Citizen is proven to be effective in developing the critical thinking skills of elementary school students, and is relevant to be applied in Pancasila Education learning that emphasizes the formation of democratic and reflective characters.